At the bottom of the totem pole. About files, witnesses and suspicious sources: - Almada, Luciana Victoria (Facultad de Ciencias Políticas y Sociales, 2021)
In 2019, Emma Song said that "introducing a book should be more like an orgy of ideas than others brought to me". The following article is guided by this spirit, these notes are intended to show connections between files, witnesses and sources, adjectivized as suspicious. An approach to sexual politics that runs through archives as a discipline, transformed over the years by the proliferation of others and from others stories . As modest witnesses, we place ourselves in Córdoba and in the recent past to reflect theoretically and methodologically, and to ask ourselves about the future of our memory(s) and sexual dissidence.